Aprovechamiento de los lodos de planta de tratamiento de aguas residuales en empresa láctea, municipio de Cogua (2019)
The treatment of domestic and/or industrial wastewater has as ultimately results the treated water and sewage sludge, the latter is a biosolid with hazardous characteristics depending on the components present in the water to be treated; therefore, it must have a suitable handling, treatment and final disposal to reduce risks or the negative impacts to human health and the environmental. Currently different uses of biosolids can be found according to physical, chemical, microbiological and hazard characteristics that it has and thus can be classify them as type A or B for their different uses based on the national legal regulations (decree 1287 of 2014).